A novel approach for securing data against adversary attacks in UAV embedded HetNet using identity based authentication scheme - Aabid Rashid Wani; Sachin Kumar Gupta; Zeba Khanam; Mamoon Rashid; Sultan S. Alshamrani; Mohammed Baz (IET Intelligent Transport Systems, 2023)
Abstract Unmanned Aerial Vehicle (UAV) integrated Heterogeneous Network (HetNet) is currently considered as one of the promising technologies. This technology helps in fulfilling high demands of bandwidth, volume, and range as per user needs. In this paper, the work is carried out by authors to assure high security for the users in such a network by incorporating an authentication‐based security known as Identity based Scheme (IBA). The IBA based implemented networks improve the confidentiality of data and the authenticity of the users. Privacy and reliability come through the entity's capacity to authenticate, sign and transact authenticated data without central directory interference. Therefore,the primary scope of this research project is to create an identity‐based authentication mechanism in HetNets that are assisted by UAVs and to secure communication against potential intruder threats. In this way, the security assurance is increased and dreadful intruder attacks are minimized. Moreover, in this research work, the implementing zones would be areas of defence for observation of a region to locate an enemy or as certain strategic features. The security rules are formulated in the coded language known as High Level Protocol Specification Language (HLPSL) and outcomes are verified through Automated Validation Internet Security Protocols and Applications (AVISPA).